Epidemiology of concurrent extrapulmonary tuberculosis in inpatients with extrapulmonary tuberculosis lesions in China: a large-scale observational multi-centre investigation. (February 2022) - Kang, Wanli; Liu, Shengsheng; Du, Jian; Tang, Peijun; Chen, Hongyan; Liu, Jianxiong; Ma, Jinshan; Li, Mingwu; Qin, Jingmin; Shu, Wei; Zong, Peilan; Zhang, Yi; et al.
Highlights: There are various forms of concurrent extrapulmonary tuberculosis (EPTB) in China. In total, 22 association rules of concurrent EPTB were identified. The association rules of concurrent EPTB varied with gender and age. ABSTRACT: Aims: A high proportion of all patients with tuberculosis (TB) present with extrapulmonary TB (EPTB), including concurrent EPTB involving more than one extrapulmonary lesion site. However, previous reports only characterized lesions of single-site EPTB cases. This study aimed to investigate epidemiological characteristics and association rules of concurrent EPTB cases in China. Methods: An observational multi-centre study of 208, 214 patients with EPTB lesions was undertaken in China from January 2011 to December 2017. Multi-variable logistic regression analysis was used to identify associations between gender and concurrent EPTB, and age and concurrent EPTB. Association rules were analysed for significance using the Apriori algorithm. Results: The most common EPTB lesion was tuberculous pleurisy (49.8%), followed by bronchial TB (14.8%) and tuberculous meningitis (7.6%). The most common type of concurrent EPTB was tuberculous pleurisy concurrent with tuberculous peritonitis (1.80%). In total, 22 association rules, including 20 strong association rules, were identified; among these, the highest confidence rates were found for tuberculous myelitis concurrent with tuberculous meningitis, and sacral TB concurrent with lumbar vertebral TB. The association rules of EPTB concurrent with other EPTB types were found to vary with gender and age. The confidence rate of tuberculous myelitis concurrent with tuberculous meningitis was higher in females (83.67%) than males, and was highest in patients aged 25–34 years (87.50%). Conclusions: Many types of concurrent EPTB were found. Greater awareness of concurrent EPTB disease characteristics is needed to ensure timely clinical diagnosis and treatment of this disease.